HUBUNGAN PELAKSANAAN SUPERVISI KEPALA RUANGAN DENGAN KINERJA PERAWAT PELAKSANA DALAM PENDOKUMENTASIAN ASKEP - Masri Saragih (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Nursing supervision is intended to lead to nurses in providing nursing care. Implementation of supervision by a good head room can affect the performance of nurses in nursing care documentation and documenting the results more efficiently if supervision is carried out by the head of the room goes well. This study aims to determine the relationship of supervision of the implementation of head room with the performance of nurses in the nursing documentation in patient wards of Sari Mutiara Medan 2015. This study used a descriptive correlation with cross sectional design. The number of samples in this study were 43 respondents were divided from each inpatient room. The sampling technique used was accidental sampling. The result showed the supervision of the head of the most space is good that 27 respondents (62.8%) and the performance of nurses in nursing care documentation that most of the good that is 30 respondents (69.85%). This shows there is a significant correlation between the implementation of the supervision of the head of the room with the performance of nurses in nursing care documentation (pvalue = 0.004) <0.05. Suggestions for hospitals need to supervise periodically the documentation of nursing for nurses is expected to be more professional in doing nursing care documentation with respect to the standards specified documentation of nursing care by hospitals,